Dampak Penambangan Timah Laut terhadap Sumber Penghidupan Rumah Tangga Nelayan di Kabupaten Meranti - Tirta Anugerah; Arya Hadi Dharmawan; Ivanovich Agusta (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2021)
Abstrak: Source of Livelihood of fishermen households in Meranti Islands regency is from fishery. The livelihood of fishermen households is influenced by condition of marine ecosystem. A slight disruption to the stability of the marine ecosystem may affect whole fishermen’s livelihood system. Tin mining activities in each operation has resulted in the degradation of coastal and marine ecosystems, giving shocking impacts on the fishermen’s livelihoods there. The purpose of this study is to analyze the level of vulnerability of livelihoods of small fishermen’s households whose fishing areas are degraded. This study uses quantitative methods supported by qualitative approach. The data was collected from twenty fishermen’s household using gillnet (tangsi) and twenty fishermen’s households using trawling. Questionnaire used as a research instrument and qualitative data collection was obtain from in-depth interviews. This study found that fishermen households using trawling method are more vulnerable to their livelihoods than fishermen households using gillnet (tangsi). Two groups of fishermen households are not only threatened with loss of their livelihoods as fishermen. At the same time, they also lost their homes due to mining activities. Keywords: vulnerability, marine degradation, fishermen, livelihood system Intisari: Sumber penghidupan rumahtangga nelayan di Kabupaten Kepulauan Meranti berasal dari aktivitas menangkap ikan. Penghidupan rumahtangga nelayan sangat dipengaruhi kondisi ekosistem laut sehingga sedikit saja terjadi guncangan pada kestabilan ekosistem laut maka keseluruhan sistem penghidupan nelayan akan terpengaruh. Aktivitas penambangan timah laut dalam setiap operasi telah mengakibatkan degradasi ekosistem pesisir dan laut sehingga memberi guncangan terhadap penghidupan rumahtangga nelayan setempat. Tulisan ini bertujuan untuk menganalisis tingkat kerentanan penghidupan rumahtangga nelayan kecil yang ekosistemnya terdegradasi. Penelitian ini menggunakan metode kuantitatif yang didukung pendekatan kualitatif. Data dikumpulkan dari 20 rumahtangga nelayan jaring tangsi dan 20 rumahtangga nelayan jaring gombang dengan menggunakan kuesioner sebagai instrumen penelitian dan wawancara mendalam untuk mendapatkan data kualitatif. Tulisan ini menemukan fakta bahwa rumahtangga nelayan gombang lebih rentan penghidupannya dibandingkan rumahtangga nelayan tangsi. Kedua kelompok rumahtangga nelayan tersebut secara umum tidak hanya terancam kehilangan sumber penghidupan sebagai nelayan, namun juga kehilangan tanah dan tempat tinggal (lost of livelihood and lost land) karena aktivitas penambangan. Kata kunci: kerentanan, degradasi laut, nelayan, sistem penghidupan